Metaverse dalam Akuntansi yang Ditinjau dari Perspektif Filosofi Realitas Plato - Adib Minanurohman; Nurul Fitriani (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2023)
Purpose: This paper aims to review the metaverse in accounting from the perspective of Plato's philosophy of reality.Method: This study uses the library research method to obtain an understanding and general description regarding the metaverse in accounting from Plato's perspective.Results: The result shows that accounting can be a tool because its development leads to a blockchain system which can later become a means of exchange in the metaverse. It turns out that the metaverse can change accounting in five ways. First, the metaverse will allow direct engagement with the client. Second, training and development of new team members that can be done through the metaverse. Third, increase employee interaction. And fourth, the existence of a metaverse will form a more intense relationship with consumers. Finally, this metaverse does have many benefits and conveniences for its users. But, despite all that, the issue of user data security is still a major concern, so it is hoped that in the future the metaverse can develop better.Implications: This research contributes to the development of literature related to the metaverse, especially accounting in terms of Plato's philosophy of reality.Novelty: This study is the first article to review how the metaverse in accounting is viewed from the point of view of Plato's philosophy of reality.